2016
DOI: 10.18632/oncotarget.12840
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of prolactin receptor induces STAT-5 phosphorylation and cellular invasion in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor in humans and is characterized with poor outcome. In this study, we investigated components of prolactin (Prl) system in cell models of GBM and in histological tissue sections obtained from GBM patients. Expression of Prolactin receptor (PrlR) was detected at high levels in U251-MG, at low levels in U87-MG and barely detectable in U373 cell lines and in 66% of brain tumor tissues from 32 GBM patients by immunohistochemical tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…A PRLR blocking monoclonal antibody showed significant antitumor activity against MCF7 breast cancer xenografts [59]. Our previous study in glioblastoma demonstrated increased PRLR expression levels and indicated some efficacy to reduce tumor cell growth by using PRLRA in experimental systems [39]. These data support the idea that the PRL system is relevant in tumorigenesis and that agents blocking the receptor or drugs conjugated with PRLRA may be of relevance for future pharmaceutical development [60].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A PRLR blocking monoclonal antibody showed significant antitumor activity against MCF7 breast cancer xenografts [59]. Our previous study in glioblastoma demonstrated increased PRLR expression levels and indicated some efficacy to reduce tumor cell growth by using PRLRA in experimental systems [39]. These data support the idea that the PRL system is relevant in tumorigenesis and that agents blocking the receptor or drugs conjugated with PRLRA may be of relevance for future pharmaceutical development [60].…”
Section: Discussionmentioning
confidence: 64%
“…It stimulates proliferation of different cell types in the body and has been linked to enhanced tumor cell growth [35][36][37]. Increased PRLR levels in tumors may therefore stimulate cancer cell growth via PRL [38,39]. Recent findings demonstrate that PRL production is not only restricted to the pituitary gland [40], which makes this theory interesting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pituitary hormone prolactin (PRL) is another component that significantly reduced by MALAT1 silencing. Interestingly, it was shown that PRL is overexpressed in GBM tumor and increases invasiveness of GBM cells by inducing phosphorylation of STAT5 ( 39 ). Expression of other signaling molecules including IL-8, VEGF-C, HB-EGF and NRG1 were also significantly reduced with MALAT1 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…A look into the most prestigious scientific journals such as the New England Journal of Medicine [ 3 ], Lancet [ 4 , 5 ] or Journals of the American Medical Association [ 6 ] reveals an impressive number of scientific publications that have been published on this condition to date. A large number of basic and clinical studies have also been published in Oncotarget recently [ 7 19 ]. However, patients and their families are traumatized by the diagnosis.…”
Section: Introductionmentioning
confidence: 99%